X-intercept Y-intercept



$x$-intercepts when $y=0$
$y$-intercepts when $x=0$

Example 1

Sketch the graphs of $y=x^2+x-2$ by stating $x$- and $y$-intercepts.

$x$-intercepts when $y=0$
\( \begin{align} \displaystyle
x^2+x-2 &= 0 \\
(x+2)(x-1) &= 0 \\
x &= -2, 1 \\
\end{align} \)
$y$-intercepts when $x=0$
\( \begin{align} \displaystyle
y &= 0^2+0-2 \\
&= -2 \\
\end{align} \)

Example 2

Sketch the graphs of $y=-x^2+3$ by stating $x$- and $y$-intercepts.

$x$-intercepts when $y=0$
\( \begin{align} \displaystyle
-x^2+3 &= 0 \\
x^2 &= 3 \\
x &= -\sqrt{3}, \ \sqrt{3} \\
\end{align} \)
$y$-intercepts when $x=0$
\( \begin{align} \displaystyle
y &= -0^2+3 \\
&= 3 \\
\end{align} \)





Your email address will not be published. Required fields are marked *